Prenatal stress increases the striatal and hippocampal expression of correlating c‐FOS and serotonin transporters in murine offspring. Issue 38 (4th August 2014) - Bielas, H.; Arck, P.; Bruenahl, C.A.; Walitza, S.; Grünblatt, E.
Abstract: Prenatal stress (PS) is a known risk factor for several psychiatric diagnoses, including schizophrenia, attention deficit hyperactivity disorder, autism, anxiety, and depression which have been associated with serotonin transporter (SERT) dysregulation. Moreover, long‐term effects in animal models associate with higher levels of immediate early genes, e.g. c‐FOS (up‐regulated in response to neuronal activity), in the brain of PS offspring. We therefore quantified the expression of both protein related mRNAs in adolescent BALB/c mice subjected to mild auditory stress on two separate days in mid gestation. SERT and c‐FOS consistently correlated in most brain regions of PS mice and controls. Moreover, two‐way ANOVAs revealed concomitantly increased levels of proteins, as well as of FOSL1 and FOSL2 mRNA, especially in the striatum and hippocampus of the PS offspring. Sex affected only and less consistently mRNA expression, yet interacted with PS, demonstrating that glucocorticoid receptor mRNA expression decreased in PS males but increased in PS females compared to the respective controls. This first finding of a correlation between SERT and c‐FOS protein expression affected by PS, together with related mRNAs, may be considered a new target for behavioral and treatment studies in offspring.